Spinal Arachnoid Cysts—Our Experience - Diyora, Batuk; Purandare, Anup; Devani, Kavin; Palave, Prakash; Dhall, Gagan; Gawali, Sagar (Asian Journal of Neurosurgery, 2024)
Introduction Spinal arachnoid cysts are rare. Most of these lesions are located in the thoracic and thoracolumbar regions. Magnetic resonance imaging is a valuable tool for understanding their location and provides important information regarding their origin and expansion. The aim of our study was to evaluate the demographics, presentations, surgical management, and outcome of a spinal arachnoid cyst.Materials and Methods All the patients from January 2003 to December 2021 who were symptomatic for spinal arachnoid cysts were taken for study. A retrospective analysis was performed. Radiological investigations were performed, and patients were graded according to the Nabors classification. Operative results were graded according to surgical technique.Results The study included 22 patients, 11 female and 11 male patients, with a male-to-female ratio of approximately 1:1. The mean age of presentation was 34.7 years (4–60 years). Of 22 patients, 15 have intradural arachnoid cysts, 7 have an intradural extramedullary arachnoid cyst, and 8 have an intramedullary arachnoid cyst. Symptoms varied from weakness in the lower limbs (50%), quadriparesis and spasticity (32%), bladder/bowel incontinence (14%), and pain (10%). Out of 22 patients, complete cyst excision was performed in 17 patients, marsupialization in 4 patients, and cystic-subarachnoid shunt in one patient. Weakness and spasticity gradually recovered over a period of time. At 1-year follow-up, all the patients had complete improvement in their weakness, spasticity, and bladder functions. No recurrence of the cyst was seen at 1-year follow-up.Conclusion Spinal arachnoid cysts are very rare in the spinal cord. Most of the lesions are located in the thoracic and thoracolumbar regions. Asymptomatic cyst requires counseling and conservative management, whereas symptomatic cyst, if operated on with surgical expertise, recurrence and complications are very low. The best surgical technique for operating these spinal arachnoid cysts is still under question, but symptom improvement is seen in all operative procedures.
Keywords: spine; arachnoid cyst; extradural; intradural; intramedullary